2020
DOI: 10.1093/eurheartj/ehaa942
|View full text |Cite
|
Sign up to set email alerts
|

Brugada syndrome genetics is associated with phenotype severity

Abstract: Aims  Brugada syndrome (BrS) is associated with an increased risk of sudden cardiac death due to ventricular tachycardia/fibrillation (VT/VF) in young, otherwise healthy individuals. Despite SCN5A being the most commonly known mutated gene to date, the genotype–phenotype relationship is poorly understood and remains uncertain. This study aimed to elucidate the genotype–phenotype correlation in BrS. Methods and results Brugada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 29 publications
4
73
0
5
Order By: Relevance
“…It was also reported that proband status, inducibility toward ventricular arrhythmias (86), arrhythmogenic substrate area, and late potentials (87) were predictors of higher risk. Our group recently proposed the SCN5A genetic status as a prognostic factor for BrS patients (12,88). In particular, SCN5A mutation carriers exhibited more pronounced epicardial electrical abnormalities and a more aggressive clinical presentation.…”
Section: Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that proband status, inducibility toward ventricular arrhythmias (86), arrhythmogenic substrate area, and late potentials (87) were predictors of higher risk. Our group recently proposed the SCN5A genetic status as a prognostic factor for BrS patients (12,88). In particular, SCN5A mutation carriers exhibited more pronounced epicardial electrical abnormalities and a more aggressive clinical presentation.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…However, variants in SCN5A have long been known to not necessarily segregate with BrS (4,11). Recently, patients harboring SCN5A variants were demonstrated to have a worse prognosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…A combined clinical and electrophysiological mapping study showed that SCN5A mutation carriers exhibit more pronounced epicardial electrical abnormalities and a more aggressive clinical presentation than non-carriers. 52 Recent data support the use of drug therapy to manage patients with catecholaminergic polymorphic VT (CPVT). In a provocative paper by Van der Werf et al, 53 no survival benefit from ICDs was shown in young CPVT patients surviving cardiac arrest.…”
Section: Nasljedne Bolesti Srca Procjena Rizika Implantabilni Kardimentioning
confidence: 99%
“…Kombinirano istraživanje kliničkog i elektrofiziološkog mapiranja pokazalo je da nosioci mutacija SCN5A pokazuju izraženije epikardijske električne abnormalnosti i agresivniju kliničku prezentaciju nego nenosioci. 52 Noviji podatci podupiru primjenu terapije lijekovima za zbrinjavanje bolesnika s katekolaminergičnom polimorfnom VT (CPVT). U provokativnom radu Van der Werfa i sur.…”
Section: Resynchronization Therapy Including His Bundle Septal and Leunclassified